PENGARUH PDRB PER KAPITA, PENGANGGURAN, KELUHAN KESEHATAN DAN PERTUMBUHAN PENDUDUK TERHADAP TINGKAT KEMISKINAN PADA KABUPATEN/KOTA DI PROVINSI BALI - Puteri, Ni Wayan Meisya Cempaka; Suasih, Ni Nyoman Reni (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 12 No 12 (2023): Vol.12.No.12. DESEMBER 2023, 2023)
Poverty is a problem faced by every country, especially in developing countries like Indonesia. Efforts are always made to minimize poverty, and even eliminate it if possible. However, in reality, poverty continues to remain an integral part of various aspects of human life. The complexity of the poverty issue continues to be a recurring focus in every developmental phase across different regions. It's worth noting that Bali Province has experienced rapid economic growth, but the unemployment rate and the number of people living in poverty remain high. Addressing the issue of poverty remains a primary focus that requires additional attention. Therefore, government policies are needed to address this problem, particularly in the districts and cities of Bali Province. This study aims to analyze the per capita Gross Regional Domestic Product (GRDP), unemployment, health complaints, and population numbers in relation to poverty in the districts and cities of Bali Province. The research employs secondary data spanning a period of 10 years, from 2012 to 2021. The study is conducted in Bali Province, encompassing 9 districts and cities. The analytical technique used is multiple linear regression analysis. The results of this study indicate that per capita GRDP does not have a negative impact on poverty in the districts and cities of Bali Province. Meanwhile, unemployment, health complaints, and population growth have a positive impact on poverty in the districts and cities of Bali Province. Keywords: Poverty, GRDP Per Capita, Unemployment, Health Complaints, Population Growth